Implementation of Islamic Religious Learning Models to Foster Environmental Character in a Nature-based Elementary School - Silvi, Eka; Arif, Muhamad; Aziz, Mohd Kasturi Nor Abd (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2025)
This study aims to analyze the Islamic Religious Education (IRE) learning model in fostering environmental care character at nature-based elementary schools and identify the challenges teachers face. The research employed a case study approach with interviews, observations, and documentation as data collection techniques. Using Robert K. Yin's framework, data analysis is performed by pattern matching, explanation building, time series analysis, and repeated observations. The findings reveal that IRE learning applies Project-Based Learning (PjBL) through stages of project design, problem identification, scheduling, research implementation, prototype development, assessment, finalization, and feedback. This model positively impacts students by increasing environmental awareness, fostering eco-friendly attitudes, strengthening social and spiritual responsibility, and reinforcing discipline and cooperation. Theoretically, this study contributes to the discourse on integrating IRE with environmental education through PjBL, while guiding teachers and schools to design IRE learning oriented toward ecological awareness. Future studies are recommended to quantitatively measure the effectiveness of PjBL, develop eco-friendly digital learning media, and conduct comparative studies across schools to identify the best implementation patterns.